1997
DOI: 10.1111/j.1365-2672.1997.tb02877.x
|View full text |Cite
|
Sign up to set email alerts
|

The survival of Staphylococcus aureus during the fermentation and storage of yoghurt

Abstract: The effect of yoghurt culture Rx on the survival of Staphylococcus aureus CCM 5984 added to milk in various concentrations was observed during the fermentation and storage of yoghurt. The end of the fermentation process (3.5 h) was only accompanied by a slight reduction. During the storage of yoghurt at 4 degrees C a 1-2 log reduction was observed. No Staph. aureus was detected in yoghurt produced from milk contaminated by 10(3) Staph. aureus cells l-1 after 48 h of cold storage. When a concentration of 10(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
0
16
0
3
Order By: Relevance
“…Also, Carfora et al [39], Basanisi et al [40], Ektik et al [41], Papadopoulos et al [42], and Usman and Mustapha [43] could isolate CoPSA from dairy products samples, and MRCoPSA and VRCoPSA were among them. The lack of dairy food samples from CoPSA could be contributed to the low pH of the samples as a result of fermentation [44], in addition that food samples originated from large scale factories, while, the occurrence of CoNS in food may result primarily from its ability to withstand adverse environmental conditions throughout the manufacturing, storage and high adaptation capacity of those micro-organisms [45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Carfora et al [39], Basanisi et al [40], Ektik et al [41], Papadopoulos et al [42], and Usman and Mustapha [43] could isolate CoPSA from dairy products samples, and MRCoPSA and VRCoPSA were among them. The lack of dairy food samples from CoPSA could be contributed to the low pH of the samples as a result of fermentation [44], in addition that food samples originated from large scale factories, while, the occurrence of CoNS in food may result primarily from its ability to withstand adverse environmental conditions throughout the manufacturing, storage and high adaptation capacity of those micro-organisms [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that several potential pathogenic bacteria (Staphylococcus aureus, Campylobacter jejuni, Salmonella spp., Shigella spp., L. monocytogenes, and E. coli O157:H7) intentionally added to yogurt or fermented milk before or after fermentation, thus simulating cases of ineffective heat treatment or postcontamination, were hardly able to survive or otherwise multiply (Alm, 1983;Čuk et al, 1987;Zúñiga-Estrada et al, 1995;Pazakova et al, 1997;Issa and Ryser, 2000;Benkerroum et al, 2002;Belessi et al, 2008;Hsieh et al, 2010;Osaili et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Similar to our observation, elimination of S. aureus by LAB at low temperatures was also reported by Estrada, Mendonza, de la Garza, and Ferado (1999), where it survived the fermentation of milk by yogurt starter culture, but was inhibited as soon as the fermentation was followed by refrigeration at 4°C. Similarly, S. aureus, which survived fermentation of yogurt for 4 h, was eliminated after 48 h of cold storage (Pazakova, Turek, & Laciakova, 1997). In general, S. aureus with counts <10 5 cfu/ml may not be a point of concern, as enough toxins will not be elucidated to cause food-borne gastroenteritis.…”
Section: Resultsmentioning
confidence: 94%